On the taxonomic validity of Indian ground spiders: V. Genera Megamyrmaekion Reuss, 1834, Sosticus Chamberlin, 1922 and Gaviphosa gen. nov. (Araneae: Gnaphosidae) - Sankaran, Pradeep M.; Caleb, John T.d. (Zootaxa, 2021)
Indian Megamyrmaekion and Sosticus species are revised, mostly based on the type material available in the National Zoological Collection, Zoological Survey of India, Kolkata. The following new synonymies are recognised: Megamyrmaekion ashae syn. nov. is synonymised with Megamyrmaekion caudatum Reuss, 1834, Megamyrmaekion kajalae syn. nov. with Drassodes luridus (O. Pickard-Cambridge, 1874), Sosticus jabalpurensis syn. nov. and Sosticus sundargarhensis syn. nov., both with the liocranid species Sphingius barkudensis Gravely, 1931 and Sosticus poonaensis syn. nov. with the liocranid species Sphingius caniceps Simon, 1906. The following new combinations are recognised: Poecilochroa jodhpurense (Gajbe, 1993) comb. nov., ex. Megamyrmaekion, Urozelotes pawani (Gajbe, 1993) comb. nov., Sphingius dherikanalensis (Gajbe, 1979) comb. nov., Sphingius nainitalensis (Gajbe, 1979) comb. nov. and Sphingius solanensis (Gajbe, 1979) comb. nov., all ex. Sosticus. All the examined type material are imaged and supplementary descriptions for P. jodhpurense comb. nov. and U. pawani comb. nov. are provided. A new monotypic genus, Gaviphosa Sankaran, 2021 gen. nov. for Gaviphosa kera Sankaran, 2021 gen. et sp. nov., featured by dorsal tibial apophysis is described and illustrated in detail from the southern Western Ghats of India.